Modeling Of Tsunami Flood Maps Along The Malang Coast Using Commit 1.8.1 And Quantum Gis 2.18.28 “Las Palmas” Software: Pemodelan Peta Banjir Tsunami di Sepanjang Pantai Malang Menggunakan Perangkat Lunak Commit 1.8.1 dan Quantum GIS 2.18.28 “Las Palmas” - Annur, Rofikoh; Sungkowo, Ari (Sunan Kalijaga Journal of Physics, 2025)
The long coastline of Malang, located in the south of Java Island, is close to the Indian Ocean, which has a subduction zone. This makes Malang Regency a potential tsunami-prone area. Therefore, a tsunami inundation map is needed as a reference for creating a tsunami evacuation map. Tsunami inundation modeling is used to estimate the worst-case tsunami impact. The modeling was conducted using ComMIT (Community Model Interface for Tsunami) 1.8.1 based on an Mw 8.7 earthquake scenario taken from the 2017 Indonesian Earthquake Source and Hazard Center distribution of megathrusts and active faults in the South Java Sea, specifically in the East Java Megathrust zone. The inundation map was created using Quantum GIS 2.18. 28 Las Palmas The tsunami inundation modeling results showed that the inundation distance varied between 0.9 and 1.9 km inland, the tsunami height on the coast varied between 8.41 and 19.63 meters with a maximum run-up of 10 meters, and the tsunami arrival time on the coast was around 30 minutes after the earthquake occurred.